PENENTUAN DOSIS DAN WAKTU REAKSI OPTIMUM EKSTRAK BUAH SAWO (Achras zapota L.) DALAM MENURUNKAN KADAR KOLESTEROL - Essy Purwaningtyas dan Rimma Hilda Kusumaningtyas (Pelita - Jurnal Penelitian Mahasiswa UNY, 2011)
This research was aimed at finding out (1) the optimum dosage of sapodilla extract in reducingcholesterol; (2) the optimum reaction time of sapodilla extract in reducing cholesterol.The method used in this research used two variables, dependent and independent variables. Theindependent variable in this research was the dosage of sapodilla extract and the reaction time ofsapodilla extract toward cholesterol, while the dependent variable was the decrease of cholesteroltowards the dosage of sapodilla extract and the reaction time which were given in different ways. Thisresearch was tested by using spectrophotometer method.The result of this research was the more the dosages of sapodilla extract given the greater theamount in decreasing the cholesterol was and the reaction between sapodilla extract and cholesteroloccurred after they were mixed in two and half hours.Keywords: determining the dosage, the optimum reaction time, sapodilla extract, amount of cholesterol